The Magic Needle : And Other Stories - Blyton, Enid; Illustrated By Biro, Val (Singapore Award Publications Limited, 2007)
Contains assorted short stories by Enid Blyton.
Include Illustrations
Originally Published : 2001.
Keywords: Children's stories -- Short stories -- Magic